Cheaters never win - Huntsman, Jon M. (FTPress Delivers elements., 2010)
This is the eBook version of the printed book. If the print book includes a CD-ROM, this content is not included within the eBook version. This Element is an excerpt from Winners Never Cheat: Even in Difficult Times (ISBN: 9780137009039) by Jon M. Huntsman. Available in print and digital formats. The surprisingly simple reminder that can keep people honest when they're tempted to stray. Why do some bright students cheat? Why do some otherwise upstanding citizens chisel on their income taxes? Why do some physically fit, talented athletes inject themselves with performance-enhancing drugs? How can some folks who profess to be religious look you in the eye, and lie? Why do some of the richest people have the hardest time parting with money for those in need?